Phylogenetic analysis of nine Impatiens species from subgenus Clavicarpa and subgenus Impatiens (Sect. Impatiens and Sect. Racemosae) based on chloroplast genomes - Yang, Mengqing; Lan, Wenxiang; Zhong, Jianhui; Ma, Hui; Huang, Xi; Huang, Meijuan; Huang, Haiquan (Frontiers in Plant Science, 2025)
IntroductionThe genus Impatiens L. ( Balsaminaceae) is one of the three most important bedding plant genera globally, valued for its medicinal, ornamental, and economic properties. However, the morphological overlap among species and the lack of genomic data have limited our understanding of their molecular phylogenetic relationships. MethodsThis study involved the sequencing of the chloroplast genomes of 9 Impatiens species, including Impatiens lateristachys, Impatiens siculifer var. porphyrea, Impatiens apalophylla, Impatiens pritzelii, Impatiens menghuochengensis, Impatiens membranifolia, Impatiens qingchengshanica, Impatiens aquatilis, and Impatiens racemosa. The study evaluated sequence divergence by comparing genomic features, repeat sequences, codon usage, IR expansion and contraction, sequence alignment, and selective pressures. It then constructed phylogenetic relationships using the maximum likelihood method, revealing the evolutionary relationships among these species. ResultsThe results indicated that the chloroplast genome sizes ranged from 151, 784 bp (I. racemosa) to 152, 628 bp (I. apalophylla), encoding between 108-115genes[77 to 81 protein-coding genes, 27 to 30 tRNA genes, and 4 rRNA genes]. Additionally, A detailed analysis was performed on the characteristics of repeat sequences, codon preferences, and IR region. Coding sections were more conserved than non-coding regions, and the IR regions were more conserved than the LSC and SSC regions, according to sequence variation and mutation hotspot analyses. The 9 species of Impatiens were classified into subgenus Clavicarpa and subgenus Impatiens, including the sections Impatiens and Racemosae, according to the phylogenetic tree. DiscussionThis study presents the chloroplast genomes of 9 species within the genus Impatiens, marking a novel attempt at using phylogenetic analysis to determine the taxonomic positions of Impatiens species. It provides new molecular evidence for the systematic and evolutionary studies of Impatiens species.